2018
DOI: 10.1103/physrevb.98.104205
|View full text |Cite
|
Sign up to set email alerts
|

Glass relaxation and hysteresis of the glass transition by molecular dynamics simulations

Abstract: As out-of-equilibrium materials, glasses continually tend to relax toward the metastable supercooled liquid state. Glass relaxation can result in a non-reversible glass transition upon a cooling/reheating cycle. Here, based on molecular dynamics simulations, we present a novel methodology combining thermal cycles and inherent configuration analysis to investigate the features of relaxation and glass transition reversibility. By considering three archetypical silicate glasses, viz., silica, sodium silicate, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 73 publications
2
17
0
Order By: Relevance
“…6c, the glass density predicted by MQ-MD simulations expectedly tends to increase upon decreasing cooling rate. This echoes the fact that glasses usually become more compact upon slower cooling rate (with the notable exception of pure silica) [14,50]. However, as the cooling rate decreases, we note that MQ-MD simulations tend to overestimate the density of sodium silicate observed experimentally, i.e., 2.45 g/cm 3 [44,51].…”
Section: Figure 6bsupporting
confidence: 56%
“…6c, the glass density predicted by MQ-MD simulations expectedly tends to increase upon decreasing cooling rate. This echoes the fact that glasses usually become more compact upon slower cooling rate (with the notable exception of pure silica) [14,50]. However, as the cooling rate decreases, we note that MQ-MD simulations tend to overestimate the density of sodium silicate observed experimentally, i.e., 2.45 g/cm 3 [44,51].…”
Section: Figure 6bsupporting
confidence: 56%
“…To correct for the thermal history difference, the T f values for the MD simulated glasses have been determined by extrapolating experimental data (Grandjean et al, 2008) the same way as shown in Figure 2A, i.e., all T f values have been scaled with a constant relative to the experimental values. The predicted T f values by this method are generally in good agreement with those determined by using the method of Liu et al (2018) (see Figure S5).…”
Section: Structure Prediction Of Potassium Borosilicate Glasses Withosupporting
confidence: 73%
“…Fictive temperatures (T f ) were found by employing the method of Liu et al (2018). This method uses local groundstate enthalpy as a function of temperature to estimate T f , giving very well-defined transitions compared to common methods of temperature-enthalpy plots as the method only considers the enthalpy of the atomic configuration at each temperature, leaving out contributions of atom dynamics.…”
Section: Structural and Thermal Analysismentioning
confidence: 99%
“…In order get some insights into the atomic structure of the glass, we use molecular dynamics (MD) simulations, which is an effective method to help to investigate and understand the atomic-scale behavior of materials and have been applied in studying and oxide glasses [6,7,[34][35][36]. We study the effect of the modifier type on the structural properties of a series of modified silicate glasses were the concentration of the modifiers was fixed to 25 mol%.…”
mentioning
confidence: 99%